In Vitro Screening of Antibacterial Activity of Endophytic Mold Extract from Mango Mistletoe Leaves (Dendrophthoe pentandra (L.) miq) - Nafisa Nafisa; Nour Athiroh Abdoes Sjakoer; Nurul Jadid Mubarakati (JSMARTech, 2023)
Endophytic microbes live in plant tissues and can be extracted to obtain active compounds. One conserved endophytic microbes is endophytic mold, found in plant tissue systems, such as leaves, flowers, branches, and plant roots. The endophytic mold was obtained from the mango parasite (Dendrophthoe pentandra (L.) Miq), a parasitic plant that contains secondary metabolites. This study aimed to determine the antibacterial properties of the endophytic mold isolates extract from mango parasite leaves against Escherichia coli. This research used an experimental method with descriptive quantitative data analysis. The research began with the purification of endophytic mold isolates, production of bioactive compounds, extraction of bioactive compounds, and determination of antibacterial activity by disc diffusion method. The results obtained from this study included four isolates containing antibacterial compounds, including isolates DBM 1, DBM 2, DBM 3, and DBM 4. Extracts of the endophytic mold of mango parasite leaves showed quite good inhibition of the growth of Escherichia coli, with the results of measuring the diameter of the largest inhibition zone of 13.17 mm, which was produced by isolate DBM 1 at a concentration of 75 ppm. Based on the results of antibacterial activity tests on endophytic molds from the leaves of the mango parasite (Dendrophtoe pentandra (L.) Miq), isolates of endophytic fungi can be used as antibacterial agents in the medium renewable category.